Analisis penerapan pajak atas dana desa di Desa Tomahalu Kecamatan Tobelo Selatan Kabupaten Halmahera Utara - Karatahi, Adelheid; Sondakh, Jullie J; Weku, Priscillia (Riset Akuntansi dan Manajemen Pragmatis, 2024)
Tomahalu is a village located in North Halmahera district, North Maluku Province. Tomahalu is one of the villages that has received village funds from the central government since 2015. Any funds received from the State cannot be separated from tax obligations in every transaction carried out. This research was conducted to determine the application of taxes on village funds in Tomahalu Village. The analytical method used in this research is qualitative research which is descriptive and based on the results of interviews with several research informants. The results of this research are that Tomahalu Village in carrying out its tax obligations is not in accordance with applicable regulations, because there are often delays in tax deposits and reporting.